A case of proximal partial priapism successfully treated with autologous clot embolisation. (22nd January 2020) - Ozden, Sami; Yildirim, Omer; Ozbek, Emin; Gulsen, Fatih
Abstract: Partial priapism is a rare disorder in literature and generally described as a contusion or thrombosis of the cavernous body of the penis secondary to blunt trauma. Because of the rarity of disease, there is not much information about the treatment. Conservative management with nonsteroidal anti‐inflammatory drug is often applied treatment. Here, we presented a proximal partial priapism treated successfully with autologous clot embolisation secondary to pelvic trauma.